Study of Vanadium Carbide Structures Based on Ve and Ev-Degree Topological Indices - Abdul Rauf; Saba Maqbool; Muhammad Naeem; Adnan Aslam; Hamideh Aram; Kraidi Anoh Yannick (Journal of Chemistry)
Vanadium is a biologically active product with significant industrial and biological applications. Vanadium is found in a variety of minerals and fossil fuels, the most common of which are sandstones, crude oil, and coal. Topological descriptors are numerical numbers assigned to the molecular structures and have the ability to predict certain of their physical/chemical properties. In this paper, we have studied topological descriptors of vanadium carbide structure based on ev and ve degrees. In particular, we have computed the closed forms of Zagreb, Randic, geometric-arithmetic, and atom-bond connectivity (ABC) indices of vanadium carbide structure based on ev and ve degrees. This kind of study may be useful for understanding the biological and chemical behavior of the structure.